Gangrenous Appendicitis in a Boy with Mobile Caecum - Keskin, Suat (Iran J Radiol, 2015)
A mobile caecum and ascending colon is an uncommon congenital disorder, and it is even rarer as the cause of an acute abdomen during childhood. This report presents the case of a 6-year-old boy with acute gangrenous appendicitis with a mobile caecum and ascending colon. Data from the surgical course, as well as laboratory and imaging studies, were acquired and carefully examined. Emergency ultrasound (US) was performed and revealed no signs of appendicitis in the right lower quadrant. Serial imaging study, including non-enhanced computed tomography (CT), was performed. An imaging study identified epigastric appendicitis with mobile caecum. Surgery was executed under general anesthesia with a median incision extending from the epigastrium to the suprapubic region. The caecum was mobile and placed in the right epigastric area, next to the left lobe of the liver and gallbladder. The gangrenous appendix was discovered posterior to the caecum and transverse colon, enlarging to the left upper quadrant. Appendectomy was executed, the gangrenous appendix was confirmed pathologically, and the patient was released 4 days later. In the US, if there are unusual clinical findings or no findings in patients with abdominal pain, CT is beneficial in determining the location of the caecum and appendix and preventing misdiagnosis in children.